KRISIS ADAB ATAU EVOLUSI ADAB Studi Fenomenologi Pergeseran Nilai Karakter pada Santri Gen Z Pondok Pesantren Bahrul Ulum Al-Hamid Ganjaran di Era Media Sosial: Persepsi Santri PP. Bahrul Ulum Al-Hamid Malang Tentang Pergeseran Nilai Adab di Era Media Sosial - Panji Nur Muhammad Sholih Sholih; M. fahrur rozi; m. rohid; Abdurrahman (Jurnal Penelitian Ilmiah INTAJ, 2026)
This study aims to uncover the essence of the lived experience of Gen Z santri at Pondok Pesantren Bahrul Ulum Al-Hamid, Ganjaran, Gondanglegi, Malang Regency, in making sense of the shift in character values — particularly adab — amid the rapid currents of social media. Using the transcendental phenomenological approach developed by Moustakas, this study involved six Gen Z santri informants selected purposively based on criteria of active involvement in the pesantren and intensity of social media use. Data were collected through in-depth phenomenological interviews consisting of 25 structured questions across six thematic blocks, with an average session duration of 60–90 minutes. The analytical process followed the transcendental stages: epoche, horizonalization, textural description, structural description, and composite description. The most significant finding is the consensus among all informants that what is occurring constitutes a crisis of adab — not an evolution — which they interpret as a genuine decline from pesantren value standards due to exposure to an unmanaged digital ecosystem. This digital threat operates more heavily on the subliminal, inner dimension of adab, while outer adab remains relatively sustained through the social pressure of the pesantren environment. This study contributes to the development of a contextual concept of adab within Islamic education in the digital era, while affirming the urgency of Islamic-value-based digital literacy as a strategic pesantren response to the challenges of digital globalization.